The relationship between exposure to Radon in Majnoon field and lung cancer risk - qusay, suhaib (Al-Nahrain Journal of Science, 2025)
The estimation of lung cancer risk resulting from exposure to radon gas emanating from the Majnoon oil fields in Basra was conducted. Previous studies indicate a notable surge in the incidence of lung cancer in 1991, with reported cases reaching 5720. In 2019, this number escalated significantly to 35864, underscoring a substantial increase in the number of cases over the years. A comprehensive assessment of lung cancer risk associated with both indoor and outdoor exposure to naturally occurring 222Rn gas was carried out. The investigation involved the use of CR-39 detectors to estimate Rn concentrations within and outside the oil field. Notably, the highest concentration was detected in sample taken at depth 1350 m was11.80 Bq/m3, while the lowest concentration was observed in sample taken at depth 1450 m was 2.18 Bq/m3. The calculated average cancer risk attributable to radon exposure was determined to be 4 deaths per million people. This underscores the potential health impact of radon gas in the Majnoon oil fields and emphasizes the need for further studies and interventions to mitigate the associated risks.